Event B - Méry, Dominique; Singh, Neeraj Kumar (Formal Methods Applied to Complex Systems: Implementation of the B Method, 2014)
This chapter provides results on the modeling and verification of systems using transition systems. The goal is to provide the basic fundamental and conceptual theories, which support Event B approach. The chapter explains how invariant properties and safety properties are defined in the framework of a transition system, which may model a program, an algorithm or a distributed system. It details the Event B language and related concepts such as events, contexts, machines and refinement. The chapter explains proof obligations (POs) generated for checking the consistency of the Event B structure. It develops three case studies, in order to illustrate the incremental and proof‐based modeling using Event B. The chapter emphasizes the notion of proof‐based patterns applied for the Event B method. It describes available tools for supporting the Event B modeling language concludes with the current and future trends for this method.